2022
DOI: 10.3329/jopsom.v40i1.56685
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Psychological Impact Among the Healthcare Workers Exposed to Covid-19 Cases in a Tertiary Hospital of Bangladesh

Abstract: Background: The unprecedented global pandemic caused by SARS-CoV-2 creates considerable psychological problems among the health care workers (HCW). The present study aimed to determine the predictors of psychological impact (in terms of depression, anxiety and stress) among the HCWs exposed Covid-19 cases in Combined Military Hospital (CMH) Dhaka. Methods: This cross-sectional study was conducted at CMH Dhaka among purposively selected 390 HCWs. Data were collected through face-to-face interview using a pre-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Several studies have conducted on healthcare workers to assess their mental state in Bangladesh during the Covid-19 pandemic. A study conducted at Bangladesh by S. M. Nurul Irfan has revealed that 21.6% of the respondents had mild to severe depressive symptoms, 43.1% of the respondents had mild to extremely severe anxiety symptoms and 24.1% of the respondents had mild to extremely severe stress symptoms [11] . Another study conducted at Bangladesh by Hasan MT et al revealed that about 67.72% physician suffers from anxiety and 48.5% of them found depressive 12 .…”
Section: Assessment For Well-being By Who-5 Index (N=50)mentioning
confidence: 99%
“…Several studies have conducted on healthcare workers to assess their mental state in Bangladesh during the Covid-19 pandemic. A study conducted at Bangladesh by S. M. Nurul Irfan has revealed that 21.6% of the respondents had mild to severe depressive symptoms, 43.1% of the respondents had mild to extremely severe anxiety symptoms and 24.1% of the respondents had mild to extremely severe stress symptoms [11] . Another study conducted at Bangladesh by Hasan MT et al revealed that about 67.72% physician suffers from anxiety and 48.5% of them found depressive 12 .…”
Section: Assessment For Well-being By Who-5 Index (N=50)mentioning
confidence: 99%